Portfolio jako narzędzie kształcenia refleksyjności przyszłych nauczycieli języków obcych - Witkowska, Magdalena (Neofilolog, 2019)
Being a reflective teacher is a highly appreciated quality of a good teacher. Reflection is considered to be essential in the job of teaching since it prompts to modify and improve the process of teaching and learning. As experts suggest reflective skills can be practiced and developed due to various teacher education models, programs and techniques. One of the techniques is a teacher portfolio that can consist of many tasks provoking teachers and teacher-trainees to reflect on their teaching. This article presents some research on the content of English teacher-trainees’ reflection and their metareflection. The research outcome provides some knowledge of what they reflect upon, if they do at all, and whether they perceive reflection as valuable in the process of learning teaching.